Finding beauty, goodness and truth in an ugly world: A personal theological and aesthetic account - Illman, Ruth (Approaching Religion, 2017)
Review of Kimberly Vrudny’s Beauty’s Vineyard: A Theological Aesthetic of Anguish and Anticipation (Collegeville, MN, Liturgical Press, 2016).